The value of control - Moritz Reis; Roland Pfister; Katharina A. Schwarz (Journal of Behavioral Decision Making, 2023)
Voluntary actions are accompanied by a sense of control over this action and its effects. Forming an appropriate sense of control (or sense of agency) has widespread consequences of individual and societal relevance. Moreover, perceived control might serve as a powerful action motivator, although this critical function has been addressed scarcely so far. Thus, in two experiments (N~=0.167em101 adults for each study), we directly examined the value of control for human agents by allowing participants to choose between financial gain and situational control. Crucially, a significant share of participants chose to be in control even when this option was less financially rewarding. That is, participants had to be offered 66% (Study 1) and 34% (Study 2) of expected asset earnings as an additional reward to make them predictably waive control. In addition to the value of objective decision rights, we also measured subjectively perceived control. This is a further extension of prior research as similar levels of objective control can lead to substantially different subjective feelings of control. Hereby, we found a share of the participants to create an illusionary sense of agency in situations of little objective control. These results portray perceived control as a powerful motivator for human behavior that comes with a unique and quantifiable value for individual agents.
Keywords: 650; choice; perceived control; reward; sense of agency